2016
DOI: 10.5137/1019-5149.jtn.19094-16.2
|View full text |Cite
|
Sign up to set email alerts
|

Is thoracolumbar injury classification and severity score (tlics) superior to ao thoracolumbar injury classification system for guiding the surgical management of unstable thoracolumbar burst fractures without neurologic deficit?

Abstract: AIm: To determine whether the Thoracolumbar Injury Classification and Severity Score (TLICS) and the Arbeitsgemeinschaft für Osteosynthesefragen (AO) Spine Thoracolumbar Injury Classification System have any superiority to each other regarding the reliability of their recommendations in the surgical management of unstable thoracolumbar burst fractures. mATERIAl and mEThODS: Fifty-five consecutive patients with thoracolumbar burst fractures undergoing instrumentation between 2010 and 2015 were analyzed retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…A notable finding is that the retrospective evaluation of the TLICS had inconsistencies with other classification systems in the treatment of burst fractures without neurological deficits. Additionally, a significant finding reported by Yuksel et al is the treatment decision discrepancy between the TLICS and AO classification systems in unstable burst fractures ( Table 2) [14]. Standardization of TL injury scores is crucial to guiding proper surgical management among treating physicians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A notable finding is that the retrospective evaluation of the TLICS had inconsistencies with other classification systems in the treatment of burst fractures without neurological deficits. Additionally, a significant finding reported by Yuksel et al is the treatment decision discrepancy between the TLICS and AO classification systems in unstable burst fractures ( Table 2) [14]. Standardization of TL injury scores is crucial to guiding proper surgical management among treating physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the AO recommendations, TLICS may be more reliable in guiding the surgical management of unstable TL burst fractures without neurological deficits, as the AO system had recommended conservative treatment. However, the patient had an unstable burst fracture [14].…”
Section: Thoracolumbar Injury Classificationmentioning
confidence: 97%
See 1 more Smart Citation
“…In past decades, the Denis 3-column system was used to classify TL fractures, but its clinical utility was limited, as it did not propose a treatment course or guided decisionmaking (9,10). Newer schemas base their classification on three components of injury: fracture morphology, neurological status, and integrity of ligamentous structures.…”
Section: Classification Systemsmentioning
confidence: 99%
“…1 The score has demonstrated acceptable reliability and validity in various studies and its recommendations were suggested to be of probable higher reliability than those of the AO thoracolumbar injury classification system particularly for guiding the surgical management of unstable burst fractures. 2 Although the resulting score can categorize patients into nonoperative (TLICS ≤ 3) and operative (TLICS ≥ 5) candidates, those patients with score 4 represent an indistinct group where either operative or nonoperative management may be conducted. Moreover, the score does not state the specifics of surgery in surgical candidates, basically, the surgical approach (anterior versus posterior) and the fixation type (open vs minimally invasive)…”
Section: Introductionmentioning
confidence: 99%